DAMPAK SOSIAL MASYARAKAT DARI AKTIFITAS PENGEBORAN MINYAK DI LAHAN PERTANIAN - Bembi Akbar Serawai; Adli; Muhammad Andri Zuliansyah (Jurnal Ilmu Komunikasi Balayudha, 2021)
Land is not only carried out as an economic activity but also as a forum for interaction for village communities. The disorientation of land use results in the narrowing of productive agricultural land and weakens the social values of the community. This study aims to analyze the social impacts that occur in rural communities due to the conversion of agricultural land to oil drilling. The location determination was carried out deliberately in the Musi Banyuasin district which is the center of the activity of converting agricultural land into oil drilling. Determination of informants using Snowball Sampling and analysis is carried out qualitatively. The results show that oil drilling activities have social impacts in the form of increased sensitivity and ease of access to education and health, decreased crime and theft of agricultural production in rural areas, the level of intimacy between communities is getting weaker, and the formation of small bosses who compete with each other as a result of high social mobility.